Agronomic Performance and Selection of Doubled-Haploid Rice Lines for Rainfed Lowland Paddy Field - da Cunha, Rojino; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Suwarno, Willy Bayuardi (Journal of Tropical Crop Science, 2020)
Rainfed lowland rice cultivation is an alternative to increase national rice production. Breeding of high yielding rice varieties suitable for rainfed lowland condition can be accelerated by using doubled-haploid (DH) as genetic materials. This study aimed at obtaining information on the agronomic performance including yields in several DH rice lines and selecting DH lines suitable for rainfed lowland paddy field. The experimental design used was a Randomized Complete Block Design with 3 replications. The treatment was thirty DH lines and 4 check varieties namely RJ31 Ciherang, RJ32 Inpari 18, RJ33 Inpari 40, and RJ43 Inpari 41. The results showed that there were variability in all agronomic performances, i.e., plant height, number of tillers, days to heading and to harvest, panicle length, number of filled and empty grains, 1000-grain weight and grain yield. The DH lines, namely RJ19 DR8-43-3-1 and RJ25 DR10-14-1-1, gave the same productivity as 4 check varieties. Index selection showed that twelve DH lines with medium number of productive tillers, early maturing, and productivity of more than 4.40 tons.ha-1 were selected for further evaluation.